Study on characteristics, properties, and morphology of poly(lactic acid)/chitosan/hydroquinine green nanoparticles - Trang Nguyen Thi Thu (Green Processing and Synthesis, 2018)
Poly(lactic acid)/chitosan (PLA/CS) green nanoparticles containing hydroquinine (Hq) were prepared by emulsion method. The content of Hq was 10–50 wt% compared with the weight total of PLA and CS. The characteristics of these nanoparticles were analyzed by Fourier transform infrared (FTIR), differential scanning calorimetry, field emission scanning electron microscopy (FESEM), and particle size analysis. The wavenumbers of C=O, C=N, OH, and CH3 groups in FTIR spectra of the PLA/CS/Hq (PCHq) nanoparticles shifted in comparision with neat PLA, CS, and Hq that proved the interaction between these components. The FESEM images and particle size analysis results showed that the basic particle size of PCHq nanoparticles ranged between 100 and 200 nm. The Hq released from PLA/CS nanoparticles in pH 2 and pH 7.4 solutions was determined by ultraviolet-visible method. The obtained results indicated that the linear regression coefficient of calibration equation of Hq in the above solutions approximates 1. The Hq release from the PCHq nanoparticles includes fast release for the eight first testing hours, and then, controlled slow release. The Hq released process was obeyed according to the Korsmeyer-Peppas kinetic model.